Effects of Agricultural Input Assistance on Households Affected by HIV/AIDS: A Case of Chirumanzu Communal Area - Jackqeline, Mutambara; Mwakiwa, Emmanuel; Mumaniki, Charity (Asian Journal of Agriculture and Rural Development, 2013)
This study was designed to ascertain the effect of humanitarian and developmental aid programmes on vulnerable households affected by HIV/AIDS. The study looked at the effect of NGOs-donated maize seed and fertilizer packs to the HIV/AIDS affected households using wards in Chirumhanzu district of Midlands province in Zimbabwe as a case study. This was done by comparing the land-use and output of maize, household income, farming assets and number of the main livestock types for the affected households before and after they received agricultural input assistance. The results from this study showed that agricultural inputs were a limiting factor to the households that are affected by HIV/AIDS. Provision of input packs enabled the households to increase cropping land by incorporating land that was not longer being utilize. In the process they managed to increase their agricultural maize production which resulted in increase in their welfare. Following the findings of this study, it is recommended that government and donors should support the vulnerable households through the provision of agricultural inputs which is a better way of achieving poverty alleviation in the medium to long term for the vulnerable households. However, for this to be achieved effectively, the support to the households affected by HIV/AIDS should be holistic including other forms of support like medical, palliative and other socio-economic support.